Komunikasi Interpersonal Petugas Jasa Kebersihan dalam Membangun Kualitas Layanan Publik : (Studi Kasus di Wahana Permainan Ferris Wheel G-Walk Citraland) - Muhammad Mudzakir; Sila Nirmala (Lembaga Pengembangan Kinerja Dosen, 2025)
Cleaning services in amusement facilities are an essential component of public service, ensuring visitor comfort and safety. However, the aspect of interpersonal communication between cleaning staff and visitors is often overlooked in service management. In fact, interpersonal communication plays a crucial role in building positive relationships, enhancing trust, and creating a satisfying service experience (DeVito, 2016). This study aims to examine how interpersonal communication by cleaning staff influences visitors’ perceptions of the quality of cleaning services at the Ferris Wheel G-Walk Citraland Palembang. The research employs a qualitative approach using a case study method. Data were collected through participant observation, in-depth interviews with three cleaning staff members, two facility managers, and five visitors, as well as visual documentation as supporting data. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing/verification. The findings indicate that interpersonal communication skills are a key factor in shaping positive visitor perceptions of cleaning services. Therefore, interpersonal communication training should be integrated into the competency development of cleaning personnel, especially in recreational public spaces that prioritize visitor experience. These findings affirm that the quality of public services is not solely determined by technical aspects, but also by the quality of human interaction during service delivery (Zeithaml, Bitner, & Gremler, 2018). Thus, interpersonal communication is a strategic component in enhancing experience-based public service quality.